Biocatalysis engineering: the big picture. (13th March 2017) - Sheldon, Roger A.; Pereira, Pedro C.
Abstract : In this tutorial review we describe a holistic approach to the invention, development and optimisation of biotransformations utilising isolated enzymes. Abstract : In this tutorial review we describe a holistic approach to the invention, development and optimisation of biotransformations utilising isolated enzymes. Increasing attention to applied biocatalysis is motivated by its numerous economic and environmental benefits. Biocatalysis engineering concerns the development of enzymatic systems as a whole, which entails engineering its different components: substrate engineering, medium engineering, protein (enzyme) engineering, biocatalyst (formulation) engineering, biocatalytic cascade engineering and reactor engineering.